Examining the relationship between academic stress and motivation toward physical education within a semester: A two-wave study with Chinese secondary school students - Yang, Menglu; Viladrich, Carme; Cruz, Jaume (Frontiers in Psychology, 2022)
The present study aimed to investigate the relationship between academic stress and motivation toward physical education through a longitudinal design with cross-lagged panel analyses. A sample of 556 Chinese secondary school students participated in the research and completed Educational Stress Scale for Adolescents at the beginning of the semester and 3 months later. The results demonstrated that academic stress factors were positively related to less self-determined motivations except that worry about grades was positively related to more self-determined motivations within each time point. In addition, we found that academic stress negatively predicted more self-determined motivations but positively predicted less self-determined motivations, whereas worry about grades negatively predicted amotivation 3 months later. Meanwhile, the influence of amotivation on despondency was also found. These results suggest that academic stress can obstruct students’ participation in physical education through an impact on self-determined motivation. Our findings also indicate that self-determined students in physical education will seek academic achievement as well, which in turn improves students’ academic status.